Multi-stakeholder platforms for the governance of agroecological transitions: Lessons from seven Agroecological Living Landscapes - ElDidi, Hagar; Navarrette, Angela; Piraux, Marc; Tristán, Maria Claudia; Vall, Eric; Chimonyo, Vimbayi; Fuchs, Lisa Elena; Singh, Sonali; Frija, Aymen (International Food Policy Research Institute, 2025)
-Agroecology can be considered a science, a practice and a movement (Wezel et al. 2020) -Recently used as a holistic approach that applies ecological principles to the design and management of food systems o Coordinated effort to build equitable, accessible and just relationship-based food systems (Gliessman 2018) -Agroecological transition (AET): key concept for systemic transformation of food systems at multiple scales o A multidimensional process that concerns various stakeholders and levels across the food system, including markets, supply chains, agricultural infrastructure, technical norms and standards, and policy -Gliessman’s (2016) Transition Pathway Framework for analyzing and scaling AETs